THE THE IMPORTANCE OF NOC IN NETWORK MONITORING - Machado, Breno; Dian, Mauricio (Revista Interface Tecnológica, 2024)
The purpose of this text is to highlight the benefits of a Network Operations Center (NOC). The NOC serves as a central hub for continuous monitoring and management of an organization’s network infrastructure, playing a crucial role in cybersecurity. Key benefits include real-time monitoring, agile problem resolution, and automated incident response. These centers ensure constant oversight and quick intervention, helping to maintain network stability and integrity, reduce downtime caused by cyber threats, and enhance operational efficiency.The integration of advanced technologies, such as artificial intelligence and IoT devices, further enhances the NOC’s ability to address evolving challenges. This integration not only strengthens network security but also optimizes organizational performance and improves customer satisfaction. As technologies advance, NOCs must continuously adapt to remain effective, becoming increasingly agile and efficient in proactively managing and mitigating network issues.
Keywords: NOC. Network. Security. Benefits.